Digital Marketing Applications - Aydin, Hatice (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2019)
To understand digital marketing, it is necessary to understand what its origin is, how it develops, and which applications it is strengthened by. This volume examines the concept of digital marketing, which constitutes a new agenda in discussions on marketing and has new applications and trends. The contributions give an overview about important technologies behind digital marketing and cover deep studies from marketing discipline that evaluate digital marketing, applications, and new trends.
Keywords: internetový marketing; Internet marketing; elektronické knihy; electronic books